Exploring C-H∙∙∙metalloaromatic interactions - Tan, Yee Seng *; Siti Nadiah Abdul Halim,; Otero-de-la-Roza, Alberto; Tiekink, Edward R. T. * (2017)
The C-H···metalloaromatic interaction is an of intermolecular contact which is less explored compared to the common secondary interactions such as hydrogen bonding and π··· π stacking. A series of 12 palladium(II) xanthate complexes was prepared by varying the xanthate side group from one carbon to six carbons, i.e. primary, secondary and tertiary hydrocarbons. All 12 complexes were crystallised and the intermolecular interactions present in each system were delineated. Among the series, 11 out of 12 palladium(II) xanthates showed at least one pair of the anticipated C-H···metalloaromatic π interaction, and up to a maximum of six pairs as identified in Pd[S2CO(neo-hexyl)]2. Further, the CH···metalloaromatic π interactions led to the formation of zero, one and even two dimensional motifs in the respective crystals. From a computational chemistry study performed on Pd[S2CO(n-propyl)]2, it is revealed that a C-H···metalloaromatic π interaction is of similar strength as intermolecular Pd···S secondary bonding which led to the dimerisation of palladium(II) xanthate in the condensed phase.